Morpho-anatomical leaf and morphological floral traits in Coffea spp. genotypes - Silva, Laricia Olária Emerick (2023)
Coffee farming plays a crucial role in the global economy and society by promoting direct and indirect employment. Coffee breeding programs have been dedicated to developing cultivars capable of overcoming various challenges in coffee production. In this regard, the phenotypic characterization of individuals within a population is essential for selecting individuals with desirable traits. The objective of this work was to investigate morpho-anatomical leaf and morphological floral traits in Coffea spp. and explore the genetic and environmental effects on these traits. To attain this objective, this work consists of three chapters. In the first chapter, the objective was to evaluate the potential of leaf anatomical traits, along with agronomic traits, for studying genetic variability in genotypes of two registered cultivars of C. canephora. Eight agronomic traits and seven leaf anatomic traits were evaluated in ten genotypes of C. canephora. Significant differences among the genotypes were observed for 13 out of the 15 traits (P < 0.05). These results evidenced the heterogeneity among the studied cultivars. Leaf anatomic traits showed the highest variations compared to agronomic traits. Five out of the seven leaf anatomical traits presented heritability values higher than 80%, with emphasis on stomatal density (95.69%) and stomatal pore length (92.72%). Cluster analysis used the Mahalanobis general distance (D2 ) as a measure of genetic dissimilarity and divided the genotypes into two distinct groups. The inclusion of leaf anatomic traits to characterize C. canephora genotypes may assist plant breeders with better genetic discrimination and with greater security in plant selection when composing cultivars. In the second chapter, the objective was to study morphological floral traits of four genotypes of C. canephora and one of C. arabica cultivated at two different altitudes (36 and 1100 m.a.s.l.). The experiment comprised coffee plantations of both species at two altitudes (and their different climatic conditions), cultivated under in full sun exposure management. The number of petals and stamens varied between five and six in C. canephora, but the number of petals and stamens was always five in C. arabica. At two altitudes, Beira Rio 8 (C. canephora) genotype stood out for presenting the highest averages for all size traits related to corolla, and stigmatic lobes. The variability in floral morphology among C. canephora genotypes was not greater at high- than at low-altitude. Overall, flower size of all studied C. canephora and C. arabica genotypes was larger at low- than at high-altitude, but the stigmatic lobes length and the ratio between stigmatic lobe length and style length and partly the ratio between anther length and stamen length were greater at high-altitude. C. arabica flowers were smaller and mostly irresponsive to altitude, in contrast with C. canephora flowers. Conducting studies on morphological traits of flowers at a greater number of altitudes can provide better insights into the potential use of these traits in viii studies of adaptability and stability of Coffea spp. genotypes to different environmental conditions, and thus contribute to genetic breeding efforts to achieve resilience of coffee cultivation in the current scenarios of climate change. In the third chapter, the objective was to identify key morphological floral traits to optimize studies of phenotypic variability and thus save time in the process of developing new cultivars. Nine floral traits were measured in 760 flowers. It was proven that the flower phenology can be used to differentiate Coffea spp. genotypes. Some C. canephora genotypes showed the largest floral structures (Beira Rio 8, Guarani, 8R, and Clementino), while the genotypes with the smallest floral structures were genotypes belonging to the same species (Z8, Verdim D, Ouro Negro 1, Tardio C, NV8, Ouro Negro 2, Bamburral, LB1, and Peneirão). Among the nine evaluated floral traits, the five - petal length, anther length, stamen length, style length, and stigmatic lobe length - were strongly correlated with the traits of the greatest weight for data variability. The correlated traits had little contribution to the data variability, permitting that their exclusion had not compromised the inference of morphological flower variability in Coffea spp. genotypes. This suggested that studies aiming at differing the Coffea spp. genotypes based on floral structures may consider the four studied traits, tube length, tube diameter, corolla diameter, and the number of floral appendages (petals or stamens). The reduction of nine to these four traits can optimize time and efficiency in data collection. In the future works, the association of selected flower morphological traits with traits related to Coffea spp. production could additionally move ahead the process of coffee breeding programs.